A study on factors influence employee commitment at Majlis Agama Islam Dan Adat Istiadat Melayu Terengganu (MAIDAMT) / Siti Norbaya Hasan - Hasan, Siti Norbaya (2015)
Business organizations are aware of the importance of employee commitment. The purpose of this study was to identify the relationship between the factors that affect employee commitment toward organization at Majlis Agama Islam Dan Adat Melayu Terengganu (MIADAMT). The dependent variable for this study was organizational commitment and the independent variables were peer support, rewards, physical environment and leadership style. In term of design and methodology, this paper is based on a review of academic research papers and survey. The primary data has been collected through questionnaire and the secondary data was being used for literature review in chapter two. The findings of the research indicated that organizational commitment was significant between peer support, rewards, physical environment and leadership style. In term of practical and implications, MAIDAMT needs to focus more on rewards variable due to it significant with organizational commitment. The biggest problem in this study was the sample size of population. Hence, there were several recommendations were suggested in chapter 5 for future researcher and industry. This is because it may help and guide other researcher to do in future.